2011
DOI: 10.1139/y11-073
|View full text |Cite
|
Sign up to set email alerts
|

Time course of acute neuroprotective effects of lithium carbonate evaluated by brain impedanciometry in the global ischemia model

Abstract: It is well known that chronic treatment with lithium gives cytoprotection from ischemia and neurodegeneration. Despite the clinical relevance, the potential effects of acute lithium treatment just before and during early stages of ischemia are not well known. Brain impedance was measured in an experimental global ischemia model, to determine these potential effects and their time course,as measured in minutes. Thiobarbital anesthetized (60 mg·kg(-1), intraperitoneal injection) male Sprague-Dawley rats were inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that lithium treatment reduces neurodegeneration parameters in experimental models [23,[40][41][42][43][44][45][46][47][48]. However, most studies on the protective actions of lithium were performed with cell lines or young animals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that lithium treatment reduces neurodegeneration parameters in experimental models [23,[40][41][42][43][44][45][46][47][48]. However, most studies on the protective actions of lithium were performed with cell lines or young animals.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled brain edema is strongly associated with disability and mortality in TBI. [7][8][9] VGSCs consist of a and b subunits. Nine Nav1 a subunit genes (Nav1.…”
Section: Introductionmentioning
confidence: 99%
“…Nine Nav1 a subunit genes (Nav1. [1][2][3][4][5][6][7][8][9], which contain the ion-selective pore and act as a voltage sensor within the cell membrane, have been identified in mammals. 10 VGSCs a subunits play an important role in different tissues.…”
Section: Introductionmentioning
confidence: 99%